Integration of Environmental Procedures and Team Cohesion: Survey of Tourism Industries in the Fez Meknes Region - SEFFAR ANDALOUSSI, Sofya; HEMMI, Mohamed (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
This article studies the impact of integrating environmental actions at the level of tourism industries, focusing on the tourism sector in Morocco. It examines the impact of integrating environmental processes on the management of these industries and on team cohesion. The paper identifies the concepts of environmental management and team cohesion. To juxtapose the literature with the field, we conducted a field survey in Morocco's oldest region, Fez-Meknes, where tourism is important and local industries took advantage of the absence of tourists during the COVID-19 period to implement several environmental actions. By implementing these processes, tourist industries can improve their brand image and make considerable savings. On the other hand, they need to consider the impact of these new practices on team cohesion. Our article will attempt to examine the relationship between the implementation of environmental initiatives and the cohesion of players in the tourism industries of the Fez-Meknes region.